ANALISIS KELAYAKAN BAHASA DALAM BUKU TEKS TEMA 1 KELAS I SEKOLAH DASAR KURIKULUM 2013 - Arif Wiyat Purnanto; Ali Mustadi (Universitas Muhammadiyah Surakarta, 2016)
This research aimed to describe language appropriateness of 2013 Curriculum text book for 1st Grade’s 1st Theme.This research was conducted with qualitative approach by document analysis method. The document utilized in this research was 1st Grade’s 1st Theme of text book which was not published by Ministry of Education and Culture. The research data was collected through content analysis utilizing validated instuments. The data was analyzed with Krippendof quantitatie analysis techniqe including data collection, sample determination, data recording, data reduction, conclusion drawing and recount. The results show that 1st book of non Ministry of Education and Culture publication has fulfilled all the determined criteria achieving good grade with 82.69% of Language Appropriateness. The weakness of this book is inappropriate materials sequence order, utilization of inappropriate words for children development, and utilization of inconsistent icons/symbols. The 2nd book of non Ministry of Education and Culture publication had fulfilled all the determined criteria achieving fair grade with 78.36% of Language Adbisability. The weakness of this book was utilization of inappropriate words for children development, and material suitability to intelectual development of the students.